“This Isn't Just a Police Issue”: Tensions between Criminal Justice and University Responses to Sexual Assault among College Students - Javorka, McKenzie; Campbell, Rebecca (American journal of community psychology, 2021)
Sexual assault among college students is both a crime and a civil rights violation under U.S. federal Title IX policy, which prohibits discrimination on the basis of sex in educational institutions. The current study sought to understand the extent to which the criminal justice system influences university Title IX proceedings, as well as potential consequences of this influence. For this study, we conducted in‐depth qualitative interviews with a sample of 22 multidisciplinary, nationally‐recognized subject matter experts in the area of campus sexual assault response. The results indicated that criminal justice concepts and goals are indeed being conflated with and influencing university Title IX proceedings. Participants also reported that criminal investigations are often prioritized over or seen as higher quality than Title IX investigations. As a result, participants described diminished educational and civil rights protections for survivors. We discuss how the community psychology values of social justice, promoting health and well‐being, and accountability to oppressed groups can guide future efforts to reduce the spread of criminal justice influence into Title IX, improve existing Title IX proceedings, and explore alternative models of accountability beyond traditional criminal and civil approaches. Highlights This study explores the influence of the criminal justice system on university Title IX proceedings. Prioritization of criminal justice responses may limit survivors' educational and civil rights. Community psychologists can contribute to social justice‐based responses to campus sexual violence. Alternative models of accountability for campus sexual violence should be explored.